2011
DOI: 10.4081/cp.2011.e34
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Behçet’s Disease with Ankylosing Spondylitis and Familial Mediterranean Fever: A Rare Occurrence

Abstract: Behçet's disease (BD) and familial Mediterranean fever (FMF), which are two separate diseases sharing some clinical features, may also coexist in the same patient. Further investigations are needed to understand whether this coexistence is due to either chance or geographical distribution patterns of these diseases or to common etiopathogenetic characteristics. Spondylarthritis as part of the clinical picture in these two diseases has been questioned and probably it is not a prominent characteristic of any of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…However, he was positive for HLA-B27 and diagnosed with concomitant ankylosing spondylitis. 21 Also, Mobini 22 described a 27-year-old patient with BD who suffered from attacks of fever, arthralgia, abdominal pain; and genetic study confirmed the diagnosis of FMF. Birlik et al 23 from our country reported a case of longstanding FMF with sacroiliitis who later developed typical characteristics of BD.…”
Section: Discussionmentioning
confidence: 99%
“…However, he was positive for HLA-B27 and diagnosed with concomitant ankylosing spondylitis. 21 Also, Mobini 22 described a 27-year-old patient with BD who suffered from attacks of fever, arthralgia, abdominal pain; and genetic study confirmed the diagnosis of FMF. Birlik et al 23 from our country reported a case of longstanding FMF with sacroiliitis who later developed typical characteristics of BD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Frigui et al reported a 35-year-old man patient who had an association of BD, familial Mediterranean fever (FMF) and HLA-B27-positive AS. 17 They proposed that spondyloarthritis should definitely be sought in case of coexistence of these diseases because it is a possible form of joint involvement in both FMF and BD. Yoo reported a 35-year-old male patient with both BD and AS, presenting with deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of FMF in different studies in Turkey was found between 0.003-0.82%. [ 3 , 4 , 20 , 21 ] A study conducted by Kisacik et al[ 22 ] demonstrated the FMF prevalence in Tokat province as 0.82%, which was higher than any other province in Turkey. [ 1 - 4 , 20 , 21 ] In our study, FMF prevalence was found as 0.6%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] There are case reports presenting FMF-BD coexistence. [ 3 ] FMF-BD coexistence can be seen as FMF with oral aphthous ulcers, aseptic meningitis, and skin manifestations; or as BD with peritonitis and pleuritis. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation